Role of Endoplasmic Reticulum Stress and Autophagy in Tumor Drug Resistance - Zhenwang Zhang (Molecular Biology & Nanomedicine, 2020)
Chemotherapy is widely used to treat tumors, either systemically or locally, and plays an important role in restricting the development of tumors. In clinic treatment for tumors, a satisfying response can be achieved when they firstly expose to the chemotherapeutic drugs. However, with anticancer drugs frequently exposing to the tumors, chemotherapy gradually becomes insensitive. The reasons for tumor drug resistance have been extensively investigated. For example, it may result from the change of its molecular target structure, apoptosis inhibition or some increased enzymes activity. With so many studies on the mechanisms of tumor drug resistance, recent researches mainly focus on the role of endoplasmic reticulum (ER) stress and autophagy in tumor drug resistance. ER stress is a kind of cellular stress condition caused by disturbance in the folding capacity because of various endogenous and exogenous insults. Autophagy, as a survival-promoting pathway, is a process of capturing, degrading, and recycling intracellular proteins and organelles in lysosomes. Accumulating evidences show that ER stress and autophagy are involved in the progression of tumors. Recently, it has been found that ER stress and autophagy play an important part in tumor drug resistance, which may provide another mechanism for drug resistance. Therefore, it is of significance to find a new way of overcoming tumor drug resistance through good knowledge of ER stress and autophagy.